Patients' satisfaction with the quality of nursing care: A cross-section study - Esraa Mohammed Alhussin; Sahar A. Mohamed; Amel A. Hassan; Ahmad R. Al-Qudimat; Alaa M. Doaib; Raniah M. al jonidy; Lina I. al harbi; Eman D. Alhawsawy (Elsevier, 2024)
Background: Patient satisfaction is currently a recognized measure of the effectiveness and quality of the healthcare system. It serves as an essential tool in raising the standard of care. This study aimed to examine patients' satisfaction with the quality of nursing care provided. Methods: A hospital-based cross-sectional study was conducted, involving 400 patients selected through a random selection method, meeting the selection criteria. Data were collected using the "Patient Satisfaction with Nursing Care Quality Questionnaire," comprising a total of 19 items. The collected data were then analyzed and interpreted using descriptive and inferential statistics. Data were analyzed using STATA software V17. Results: The study revealed that the highest level of satisfaction (mean 2.31, SD 1.33) was observed in the coordination of care after discharge, specifically nurses' efforts to cater to patients' needs after they left the hospital. The lowest satisfaction level was related to privacy, with provisions for patients' privacy by nurses scoring 3.9 (SD 1.00). Overall, questionnaire scores ranged from 2.31 to 3.9, with an average score of 3.26 (SD 0.64). Conclusion: Overall, patients expressed general satisfaction with the inpatient nursing care they received, and their perceived needs and care expectations from nurses significantly influenced their satisfaction levels. Therefore, we recommend that hospital administrators regularly assess patient satisfaction levels and provide specialized on-the-job training to nurses to enhance their ability to meet patients' needs and increase their overall satisfaction.